PENGEMBANGAN LKPD BERBASIS GERMAG PADA PEMBELAJARAN IPAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Putri Pratama, Winda; Ika Rahayu Nita, Cicilia; Gutama, Andika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Science learning at SDN Bandungrejosari 1 Malang still faces challenges in improving student engagement and meaningful understanding, especially on magnetic properties. This study aims to determine the feasibility, practicality, and effectiveness of developing GERMAG-based LKPD to improve students’ learning outcomes. This research used a Research and Development (R&D) method with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. The subjects involved teachers and fifth-grade students through limited and wider trials. Data were collected using validation sheets, questionnaires, and pre-test and post-test.The results showed that the LKPD obtained a material expert validation score of 94% (very feasible) and a language expert score of 60% (quite feasible). The practicality test showed 93% from teachers and 94% from students (very practical). The effectiveness was indicated by an increase in learning outcomes from a mean pre-test score of 45.00 to 93.39 in the post-test, with an N-Gain of 0.90 (very effective), supported by a paired sample t-test with a t-value of 19.10 and significance < 0.05. In conclusion, the GERMAG-based LKPD is feasible, practical, and effective for elementary science learning.